1985
DOI: 10.1128/jb.164.2.646-652.1985
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an Escherichia coli mutant deficient in phosphoenolpyruvate carboxylase catalytic activity

Abstract: A mutant Escherichia coli (Ppcc') which was unable to grow on glucose as a sole carbon source was isolated. This mutant had very low levels of phosphoenolpyruvate carboxylase activity (approximately 5% of the wild type). Goat immunoglobulin G prepared against wild-type phosphoenolypyruvate carboxylase cross-reacted with the Ppccenzyme. The amount of enzyme protein in the mutant cells was similar to that found in wild-type cells, but it had greatly diminished specific activity. The catalytically less active mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…However, the TCA cycle cannot, under steady-state conditions, supply all of the metabolite required for biomass production. This prediction is consistent with experimental data that has shown E. coli is unable to grow on glucose minimal media without the PEP carboxylase enzyme (Coomes et al, 1985;Kornberg, 1966aKornberg, , 1966b.…”
Section: Observed Regulation Patterns Are Consistent With Identified supporting
confidence: 92%
“…However, the TCA cycle cannot, under steady-state conditions, supply all of the metabolite required for biomass production. This prediction is consistent with experimental data that has shown E. coli is unable to grow on glucose minimal media without the PEP carboxylase enzyme (Coomes et al, 1985;Kornberg, 1966aKornberg, , 1966b.…”
Section: Observed Regulation Patterns Are Consistent With Identified supporting
confidence: 92%
“…After 24 h the absorbance increased to 1.54 and 1.22, respectively. It has been observed that E. coli cells containing low PEPC activity take longer to adapt to and grow poorly in minimal medium [20,25]. The decreased cell growth indicated that Gly 829 PEPC might have lower activity than wild-type enzyme.…”
Section: Gly 829 Mutationmentioning
confidence: 99%
“…Likewise, deletion of carbon dioxide and water transport and exchange reactions caused compatibility loss across all designs. Pyruvate carboxylase (PPC) is an important reaction to channel carbon flux through the Krebs cycle (56), and hence, deletion of PPC reduces compatibility in most modular cell designs with an average CL of 43%.…”
Section: Analysis Of Potential Tradeoff Between Robustness and Modularity Can Identify Conserved Metabolic Featuresmentioning
confidence: 99%